A teaching and learning experience in civil procedure based on a complex case: the facts are ESTAO SO NOS AUTOS - Chiuzuli, Danieli Rocha; Aspe (GVcasos, 2024)
Purpose: The purposes of this report are to record a teaching and learning experience; to problematize a teaching dynamic based strictly on the idea of a process as a document and a strictly normative view of the subject; and to strengthen dialogues with other university contexts for pedagogical dialogue and possible impacts on subject formats. Scope: To present a teaching and learning experience on the subject of appeals in civil proceedings based on a complex historical disaster case in the Barcarena (PA) region. Its objectives are: Relevance: The relevance of the experience lies in the challenging call for the class to occupy various procedural positions with varying degrees of complexity, and its conduct throughout the semester, concerned with a formative perspective for the students involved. Originality: The interdisciplinary nature of the case and the complexity of the social context surrounding it allowed for the construction of a critical experience, contextually situated and with an applied perspective of legal-procedural knowledge. Keywords: Civil procedure; Appeals; Complex case; Disaster; Interdisciplinarity. Objetivo: Os objetivos desse relato sao registrar uma experiencia de ensino e aprendizagem; problematizar uma dinamica de ensino baseada estritamente em uma ideia de processo como documento e uma visao estritamente normativa sobre o tema; e estreitar dialogos com outras contextos universitarios para interlocucao pedagogica e possiveis impactos nos formatos de disciplinas no tema. Escopo: Relatar uma experiencia de ensino e aprendizagem sobre o tema de recursos no processo civil baseada em um caso complexo de um desastre e historico na regiao de Barcarena (PA). Relevancia: A relevancia da experiencia esta na convocacao desafiadora de a turma ocupar diversas posicoes processuais com diferentes graus de complexidade e sua conducao ao longo do semestre preocupada com uma perspectiva formativa das/os estudantes envolvidos. Originalidade: A interdisciplinaridade do caso e a complexidade do contexto social que o circundam permitiram a construcao de uma experiencia critica, contextualmente situada e com uma perspectiva aplicada do conhecimento juridico- processual. Palavras-chave: Processo civil; Recursos; Caso complexo; Desastre; Interdisciplinaridade.